2014
DOI: 10.1371/journal.pone.0092850
|View full text |Cite
|
Sign up to set email alerts
|

Total Nitrogen Concentrations in Surface Water of Typical Agro- and Forest Ecosystems in China, 2004-2009

Abstract: We assessed the total nitrogen (N) concentrations of 28 still surface water (lake and pond), and 42 flowing surface water (river), monitoring sites under 29 typical terrestrial ecosystems of the Chinese Ecosystem Research Network (CERN) using monitoring data collected between 2004 and 2009. The results showed that the median total N concentrations of still surface water were significantly higher in the agro- (1.5 mg·L−1) and oasis agro- ecosystems (1.8 mg·L−1) than in the forest ecosystems (1.0 mg·L−1). This w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…This not only increased Chinese fresh water use (Piao et al 2010), but also heavily polluted Chinese main rivers (Xu et al 2014) and thus eutrophication is abundant in Chinese coastal waters (Tang et al 2006a). In my PhD research, I therefore focus on understanding the trends in nutrient export by Chinese rivers, causes of river pollution and assess solutions to reduce the consequent eutrophication problems in Chinese coastal areas.…”
Section: Motivationmentioning
confidence: 99%
See 4 more Smart Citations
“…This not only increased Chinese fresh water use (Piao et al 2010), but also heavily polluted Chinese main rivers (Xu et al 2014) and thus eutrophication is abundant in Chinese coastal waters (Tang et al 2006a). In my PhD research, I therefore focus on understanding the trends in nutrient export by Chinese rivers, causes of river pollution and assess solutions to reduce the consequent eutrophication problems in Chinese coastal areas.…”
Section: Motivationmentioning
confidence: 99%
“…In general, these studies confirm an increase in fluxes of dissolved nutrients by rivers since the 1970s, except for Powers et al (2016) who showed a declining trend in P export by the Yangtze since 1970. Some experimental studies also report on nutrient pollution problems for inland water systems (Huang 2015;Xu et al 2014) and estuaries (Liu et al 2009b;Tong et al 2015). For example, Xu et al (2014) indicate that many Chinese rivers like Huai, Hai, Yellow and river deltas today have concentrations of nutrients at levels that do not allow for human consumption.…”
Section: Trends In Nutrient Export By Riversmentioning
confidence: 99%
See 3 more Smart Citations